Web-Based Archiving Information System At The Ministry of Public Works and Housing Province of Jambi - Maulana, Ade Novia; Pelisa, Egidia Ratu; Afriadi, Hery (Journal of Computer Networks, Architecture and High Performance Computing, 2024)
This research was conducted at the Jambi Province Public Works and Public Housing Office (PUPR). This research is entitled "Design of a Website-Based Archiving Information System at the Jambi Province Public Works and Public Housing Office (PUPR)". The purpose of this research is to document the process of designing an information system that functions to provide information to the PUPR Office of Jambi Province. This research was conducted qualitatively by conducting interviews and observations with the PUPR Office of Jambi Province to complete the research. The document filing system of the Jambi Province PUPR Office was designed using the prototype method. As a result of the analysis and observations made, it can be concluded that one effective way to facilitate the work of employees in finding documents is to build a web-based archiving information system. This system is expected to produce information quickly, precisely, and accurately without reducing the value of the information itself.